Mammalian cell surface display for monoclonal antibody-based FACS selection of viral envelope proteins. Issue 7 (3rd October 2017) - Bruun, Tim-Henrik; Grassmann, Veronika; Zimmer, Benjamin; Asbach, Benedikt; Peterhoff, David; Kliche, Alexander; Wagner, Ralf
ABSTRACT: The elicitation of broadly and efficiently neutralizing antibodies in humans by active immunization is still a major obstacle in the development of vaccines against pathogens such as the human immunodeficiency virus (HIV), influenza virus, hepatitis C virus or cytomegalovirus. Here, we describe a mammalian cell surface display and monoclonal antibody (mAb)-mediated panning technology that allows affinity-based selection of envelope (Env) variants from libraries. To this end, we established an experimental setup featuring: 1) single and site specific integration of Env to link genotype and phenotype, 2) inducible Env expression to avoid cytotoxicity effects, 3) translational coupling of Env and enhanced green fluorescent protein expression to normalize for Env protein levels, and 4) display on HEK cells to ensure native folding and mammalian glycosylation. For proof of concept, we applied our method to a chimeric HIV-1 Env model library comprising variants with differential binding affinities to the V3-loop-directed mAbs 447–52D and HGN194. Fluorescence-activated cell sorting selectively enriched a high affinity variant up to 56- and 55-fold for 447–52D and HGN194, respectively, after only a single round of panning. Similarly, the low affinity variants for each antibody could be selectively enriched up to 237-fold. The binding profiles of membrane-bound gp145 and soluble gp140 chimeras showed identical affinity ranking, suggesting that the technology can guide the identification of Env variants with optimized antigenic properties for subsequent use as vaccine candidates. Finally, our mAb-based cellular display and selection strategy may also prove useful for the development of prophylactic vaccines against pathogens other than HIV.